Acute symptomatic seizure prevention with perampanel in moderate and severe traumatic brain injury: a retrospective comparison with levetiracetam - Nakao, Junzo; Kashiwagi, Hideki; Yoshimura, Kohei; Kambara, Akihiro; Kotera, Ryusuke; Honda, Kotaro; Amemiya, Yu; Hatakeyama, Junji; Sakakibara, Ken; Yamakawa, Kazuma; Kawabata, Shinji; Wanibuchi, Masahiko; et al. (Frontiers in Neurology, 2025)
BackgroundAcute symptomatic seizures (ASS) occurring within 7 days after traumatic brain injury (TBI) may exacerbate secondary brain injury via excitotoxicity and elevated intracranial pressure. They are also risk factors for post-traumatic epilepsy (PTE). However, the optimal anti-seizure medication for preventing ASS remains unclear. This study aimed to compare the effectiveness of perampanel (PER) versus levetiracetam (LEV) for ASS prevention in patients with moderate to severe TBI.MethodsWe conducted a retrospective cohort study including 32 patients with moderate to severe TBI who received either LEV (n = 19) or PER (n = 13) as prophylactic anti-seizure therapy. The primary outcome was the incidence of ASS within 7 days post-injury. Secondary outcomes included PTE development, psychiatric adverse events (PAEs), and functional outcomes assessed by the Glasgow Outcome Scale–Extended (GOS-E) at 3 months. Incidence rates were compared between groups using appropriate statistical tests.ResultsThe incidence of ASS was significantly lower in the PER group (7.7%) compared to the LEV group (42.1%) (OR 0.115, p = 0.050), despite a higher prevalence of cerebral contusions in the PER group. There were no significant differences in the incidence of PTE (23.1% vs. 26.3%, OR 0.84, p > 0.99), PAEs (23.1% vs. 26.3%, p > 0.99), or favorable GOS-E scores (38.5% vs. 26.3%, p = 0.707) between the PER and LEV groups.ConclusionPER demonstrated a significant advantage over LEV in preventing ASS following moderate to severe TBI. Given its comparable psychiatric safety profile and functional outcomes, PER may be a promising therapeutic option for acute seizure prophylaxis in this population. However, further prospective studies with larger sample sizes are warranted to validate these findings.